Pentamethylquercetin Inhibits Hepatocellular Carcinoma Progression and Adipocytes-induced PD-L1 Expression via IFN-γ Signaling - Li, Zhi; Gao, Wen-Qi; Wang, Peng; Wang, Tian-Qi; Xu, Wen-Chao; Zhu, Xin-Yu; Liu, Hui (Current Cancer Drug Targets, 2020)
Background: Obesity is a significant risk factor for the development of types of cancer. Programmed death 1 and its ligand programmed death-ligand 1 (PD-L1) play a crucial role in tumor immune escape. Although, the role of PD-L1 in obesity-associated hepatocellular carcinoma (HCC) remains unknown. We previously showed that the natural flavonoid pentamethylquercetin (PMQ) possesses anti-obesity properties. Objective: This study was designed to investigate the effects of PMQ on the development of HCC in obese mice and whether PMQ regulates PD-L1 and expression in HCC. Methods: Monosodium glutamate-induced obese mice were inoculated with H22 tumor cells. Tumor volumes and weights were measured. In vitro, 3T3-L1 preadipocytes were differentiated and lipid accumulation was measured by oil-red staining, and IFN-γ level was detected by Elisa. Hepatoma HepG2 cells were treated with conditional media from 3T3-L1 adipocytes (adi-CM). Western blotting was applied to detect PD-L1 protein levels in tumor tissue and HepG2 cells. Results: Compared with control mice, H22 tumors grew faster and exhibited higher PD-L1 protein levels in obese mice. PMQ inhibited H22 tumor growth and reduced PD-L1 expression in tumor tissues. PD-L1 protein level was elevated in adi-CM-treated HepG2 cells. IFN-γ was detectable in adi-CM and exogenous IFN-γ induced PD-L1 expression in HepG2 cells. PMQ affected the differentiation of 3T3-L1 preadipocytes, decreased the level of IFN-γ secreted by adipocytes and downregulated adi-CM-induced PD-L1 expression in HepG2 cells. Conclusion: PMQ could inhibit HCC progression in obese mice at least in part through down-regulating adipocytes-induced PD-L1 expression via IFN-γ signaling.
Keywords: Pentamethylquercetin